The role of adjustment to university life in the academic performance of international students - Usman, Tasneem; Siva, Chris; Mujumdar, Swati (Journal of International Students, 2026)
Australian universities have seen a significant increase in Asian international students. In the current higher education environment, these students encounter various challenges in their adjustment to a new university environment, making it necessary to monitor their academic progress. The current study predicted a positive relationship between university adjustment and academic performance among first-year Asian international students in Australia. An online survey was used to collect data from 64 first-year undergraduate Asian international students at Monash University, Australia. The results revealed that adjustment to university is a significant predictor of academic performance. This supports past findings that students are negatively impacted academically if they struggle to adjust socially and emotionally to university and highlights the need for universities and home country schools to offer additional interventions to help Asian international students.